Answer:
![(x+3)^2+(y-2)^2=9](https://img.qammunity.org/2023/formulas/mathematics/college/7kuitx94uy6f7nwgmjbda387s5mon6m878.png)
Explanation:
Equation of a circle
![(x-a)^2+(y-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/ilekd9w5v3ytefhk3unvr8rhka2u3mptc6.png)
where:
- (a, b) is the center
- r is the radius
From inspection of the diagram, the center of the circle appears to be at point (-3, 2), although this is not very clear. Therefore, a = -3 and b = 2.
Substitute these values into the general form of the equation of a circle:
![\implies (x-(-3))^2+(y-2)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/upx5kx4uosgntzrx8jy1l4mn0vic2rpnpa.png)
![\implies (x+3)^2+(y-2)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/hl8gmpacsoybfk74kqhue0xenmg6vi8wj4.png)
Again, from inspection of the diagram, the maximum vertical point of the circle appears to be at y = 5. Therefore, to calculate the radius, subtract the y-value of the center point from the y-value of the maximum vertical point:
⇒ radius (r) = 5 - 2 = 3
Substitute the found value of r into the equation:
![\implies (x+3)^2+(y-2)^2=3^2](https://img.qammunity.org/2023/formulas/mathematics/college/k9dnstrsrxjqiq5w1r81fz43nlmolw0h91.png)
Therefore, the final equation of the given circle is:
![\implies (x+3)^2+(y-2)^2=9](https://img.qammunity.org/2023/formulas/mathematics/college/lyq3rf3nujy3z328b9hc3jgbi2nlkfyb4f.png)